2015
DOI: 10.1159/000370315
|View full text |Cite
|
Sign up to set email alerts
|

Central Centrifugal Cicatricial Alopecia Presenting with Irregular Patchy Alopecia on the Lateral and Posterior Scalp

Abstract: Background: Central centrifugal cicatricial alopecia (CCCA) is the most common cause of scarring alopecia among women of African descent which affects the central scalp and spreads centrifugally but spares the lateral and posterior scalp. Objectives: The objective of this study is to report on a new clinical variety of CCCA presenting with patchy alopecia involving the lateral and posterior scalp in addition to the central scalp. Materials and Methods: We reviewed the medical records and the clinical, dermatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Other dermoscopic features of CCCA include hair shaft variability, perifollicular erythema, broken hairs as black dots inside the follicular opening or as short broken shafts, pigmented asterisk-like macules with sparse terminal and vellus-like hairs, and scattered white patches [4,[62][63][64] (Fig. 8).…”
Section: Scarring Alopeciamentioning
confidence: 99%
“…Other dermoscopic features of CCCA include hair shaft variability, perifollicular erythema, broken hairs as black dots inside the follicular opening or as short broken shafts, pigmented asterisk-like macules with sparse terminal and vellus-like hairs, and scattered white patches [4,[62][63][64] (Fig. 8).…”
Section: Scarring Alopeciamentioning
confidence: 99%
“…Interestingly, all three studies came from the same authors—Miteva and Tosti and we think that the cases in these studies may be overlapping. The most frequent trichoscopic findings in these studies were honeycomb pigmented network, peripilar white halo, pinpoint white dots, terminal hairs, vellus hairs, white patches, erythema and scaling . The less frequent features which included asterisk‐like brown blotches, broken hairs and dark peripilar halo were highly specific for CCCA (>90% specificity for all three features) .…”
Section: Resultsmentioning
confidence: 70%
“…Central centrifugal cicatricial alopecia (CCCA) is more common among African American women and presents clinically as a central area of progressive hair loss over vertex expanding towards the periphery . Only three studies describing the trichoscopy of CCCA were found . Interestingly, all three studies came from the same authors—Miteva and Tosti and we think that the cases in these studies may be overlapping.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations